Evolution of care during pregnancy and childbirth in the extreme south of Brazil - Juraci A. Cesar; Raul A. Mendoza-Sassi; Luana P. Marmitt (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVES To describe the evolution of care during pregnancy and childbirth among postpartum women living in the municipality of Rio Grande, Southern Brazil, using data from surveys carried out every three years between 2007 and 2019. METHODS Within 48 hours after delivery, a single, standardized questionnaire was applied to all mothers who had children in local hospitals and met the inclusion criteria. Demographic and reproductive characteristics, lifestyle habits, socioeconomic level of the family, and care received during pregnancy and childbirth were investigated. In the analysis, the chi-square test for linear trend was used to assess the distribution of indicators per survey. RESULTS A total of 12,645 parturients were interviewed (98% of the women eligible to participate in the surveys). In the period evaluated, the proportion of births fell 35% among adolescents and increased 25% among women aged 35 years and over. Mothers gained, on average, two years of schooling, and their families experienced an important economic improvement, followed by loss of income in the last survey. Maternal smoking, before and during pregnancy, fell by half. The rate of mothers who started prenatal care in the first trimester and the number of consultations and laboratory tests increased. Almost 60% of prenatal consultations and 80% of births took place in the Brazilian Unified Health System. In 2019, vaginal delivery was once again the most common. The rates of low birth weight (9%) and prematurity (17%) virtually remained unchanged. CONCLUSIONS We found an important change in the reproductive profile and increased coverage of various prenatal care and delivery services. Children continue to be born well, but low birth weight and prematurity remain endemic.